Avaliação de modelos de sinterização por fluxo viscoso e determinação da taxa de crescimento de cristais e fração cristalizada em vidros - Reis, Raphael Midea Cuccovia Vasconcelos (2012)
Glass-ceramics are materials obtained from the controlled crystallization of glass. The properties of these materials are controlled by the nature and proportions of the crystalline phases and residual glass present. Sintering with concurrent crystallization of glass powders is one of the routes for the development of these materials. One of the few models that describe sinter-crystallization is the Clusters model, which allows one to calculate the density of sintered compacts by knowing composition-dependent properties, such as viscosity (η), crystal growth rate (U) and surface tension (γ), and process-dependent parameters, such as particle size distribution and the density of surface nucleation sites (NS). The determination of input parameters for the model can be labor-intensive, which may difficult its use. In this work a critical assessment of the Clusters model and its bases was performed by checking its predictions against results of sintering of spherical and jagged diopside glass particles. Frenkel s model was capable of describing the initial stages of sintering only qualitatively, requiring an adjusting factor of ~1/3. With this correction, the Modified Clusters model described the powder densification in different conditions well. The effect of crystallization was slightly underestimated by the model, which could be explained by a mechanism of Ns increase in the pores surfaces as observed in a previous work. It has been demonstrated that the jagged particles increasingly round during the heat treatment causing the densification rate to gradually approximate that of spherical particles. Additionally, a model for the determination of crystallized fraction from the surface of particles was derived and can be applied for sintered particles or crystallization DSC studies. A new technique capable of the determination of the crystal growth rate in a temperature range using a single DSC run was developed and successfully tested for three different glasses.